Acute Headache as an Emergency Presentation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
A consecutive series of 150 children (aged 2 to 18 years) who presented to an emergency department with abrupt onset of severe headache were evaluated prospectively at the Children's Hospital of the King's Daughters, East Virginia Medical School, Norfork.